Turbine vibration condition monitoring in region 3 - Mousavi, Seyed Ali; Taghipour, Mohammad (Mechanical Engineering Advances, 2023)
The present study aims to investigate the vibration monitoring status in region three of gas transmission operations in Iran. Vibration monitoring is a strong tool for troubleshooting and protecting equipment (turbines). For this purpose, the vibration condition monitoring systems in a gas compression station have been studied. The number and location of vibration sensors, vibration signal transmission to the control room, alarm and stop command, and the ability to perform advanced vibration analysis for troubleshooting and data storage are taken into consideration. The favorable situation of vibration monitoring is provided for the purpose of comparison and conclusions about the status of vibration monitoring and needs have been made.